2010
DOI: 10.1093/abbs/gmq058
|View full text |Cite
|
Sign up to set email alerts
|

Integrin β4 was downregulated on the airway epithelia of asthma patients

Abstract: The shedding of airway epithelial cells and loss of epithelial functional homeostasis are major pathological characteristics of asthma; however, the mechanism underlying these pathologies remains obscure. Our previous work showed that there were three variation sites in 5 0 flanking region of integrin b4 in asthma patients, which was correlated with decreased expression of integrin b4 in peripheral leukocytes. Integrin b4 is an important structural adhesion molecule on airway epithelia to keep the structural a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 25 publications
3
31
0
Order By: Relevance
“…The downregulation of integrin β4 expression was verified by real-time PCR and western blot. Furthermore, our group has also demonstrated that integrin β4 was downregulated in airway epithelial cells of asthmatic patients[26].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The downregulation of integrin β4 expression was verified by real-time PCR and western blot. Furthermore, our group has also demonstrated that integrin β4 was downregulated in airway epithelial cells of asthmatic patients[26].…”
Section: Discussionmentioning
confidence: 84%
“…The integrin β4 gene knock-out mice were shown to have cell cycle and adhesion defect[29]. As the first cell barrier to outer allergens, the airway epithelial cells showed a decreased wound repair and anti-oxidation ability after integrin β4 was downregulated[26], [30], [31]. Furthermore, downregulation of integrin β4 expression in airway epithelial cells could impair the antigen presentation ability of these cells, which further regulates airway inflammation reaction in allergic asthma[32].…”
Section: Discussionmentioning
confidence: 99%
“…The effective ITGB4 siRNA and control siRNA were annealed and ligated into the new pGCSIL-PUR vector to create an ITGB4 siRNA expression vector and a control expression vector (Genechem, China, Shanghai) [14]. All plasmids were sequenced to confirm that they were correct.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous work demonstrated that structural adhesion molecule integrin β4 (ITGB4) is downregulated in asthma airway epithelial cells. As the first cell barrier to outer allergens, the airway epithelial cells showed a decreased wound repair and anti-oxidation ability after ITGB4 was downregulated [14], [15]. ITGB4 is an important adhesion molecule that mediates the anchoring of airway epithelial cells to the basal membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Bronchial epithelial cells line the surface of airways, forming the first barrier to the external environment and play a critical role in the stabilization of airway microenvironment homeostasis. Increasing evidence indicates that bronchial epithelial cell lining is not merely a simple mechanic barrier that segregates the outside environment from the internal environment, but is also engaged in the regulation of local immune responses by producing cytokine and chemokines [Pichavant et al, 2003; Liu et al, 2010]. Moreover, bronchial epithelial cells express major histocompatibility complex (MHC) class I and class II molecules and co‐stimulatory molecules such as the B7 family and toll like receptors.…”
mentioning
confidence: 99%